The Makey Makey Inclusive Tangible Interface and its Educational Perspectives - Guarda, Graziela Ferreira; Fausto, Ilma Rodrigues de Souza; García-García, Julián Alberto; Braz, Ruth Maria Mariani; Leta, Fabiana Rodrigues; Pinto, Sérgio Crespo Coelho da Silva (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2022: Anais do XXXIII Simpósio Brasileiro de Informática na Educação, 2022)
Traditional human-computer interaction using a keyboard and mouse attached to a computer has been modified with the emergence of technologies that incorporate resources into clothing, furniture and everyday objects. These technologies open up new opportunities for designers to create innovative forms of interaction based on gestures, body movements or physical manipulation of real objects. One such innovation is the tangible interface, which allows computer users to interact with digital systems through the manipulation of physical objects. The Makey Makey interface, for example, is a printed circuit with a microcontroller that allows everyday objects to be used as computer keys. This paper presents a literature review of reported experiences with Makey Makey, the objective being to explore new educational and inclusive perspectives. For that, the main researches related to Makey Makey from 2012. The methodology used is characterized by the Goal-Question-Metric (GQM) protocol and included 14 articles in total. The results showed that the circuit can be used in several contexts, with important reports from the medical field with patients with cerebral palsy from the perspective of inclusion and motivational activities with the elderly. In addition, it was possible to verify that the contexts are varied, including entertainment, fun, games and a multitude of possibilities in the pedagogical area, especially if we consider their insertion in Early Childhood Education, integrating music and stimulating inventiveness.